Diagnostic challenges in reporting a case of extraskeletal Ewing’s sarcoma of the prostate in a young Indian adult - Deka, Muktanjalee; Kalita, Lachit; ROY, SHRIYA; Konwar, Ranjumoni; Choudhury, Binoy Kumar (Indian Journal of Case Reports, 2026)
Extraosseous prostatic Ewing’s sarcoma (ES) in young adults is extremely rare. We present a case of locally advanced prostate ES/primitive neuroectodermal tumor (PNET) in a 28-year-old male. He presented with difficulty in micturition and defecation for 6 months. On magnetic resonance imaging, a mass lesion was found involving the central and peripheral zones of the prostate, and it was provisionally diagnosed as a neoplastic lesion with a differential diagnosis of lymphoma or a neuroendocrine tumor. A transrectal ultrasound-guided fine needle aspiration cytology and needle biopsy, followed by histopathological examination, and immunohistochemistry confirmed the diagnosis of Extraosseous ES. The patient underwent a cystoprostatectomy followed by multi-agent chemotherapy. Presently, the patient is alive and is being followed up regularly. Nevertheless, this tumor has a very poor prognosis, with the longest reported survival of 24 months.